Relative perioperative analgesic efficacy of single-shot serratus anterior plane block versus thoracic paravertebral block in breast and thoracic surgeries – A systematic review and meta-analysis of randomised controlled trials - Jeetinder K. Makkar; Narinder P. Singh; Bisman Jeet Kaur Khurana; Preet M. Singh (Indian Journal of Anaesthesia)
Background and Aims: Various regional analgesia techniques, such as thoracic paravertebral (TPV) and serratus anterior plane (SAP) blocks, have been employed to manage postoperative pain following chest wall surgery. However, the comparative analgesic efficacy of these two approaches remains uncertain. This systematic review and meta-analysis aimed to assess the relative analgesic efficacy of these blocks in chest wall surgeries, including breast and thoracic procedures. The primary objective was the time to first rescue analgesia, and the secondary objective encompassed opioid consumption within 24 h, pain scores at different time intervals, opioid-related adverse effects and block-related complications. Methods: A systematic search for randomised controlled trials (RCTs) was conducted in PubMed, EMBASE and Scopus databases, covering studies from their inception to September 2023. We included active treatment arms from RCTs comparing these analgesic modalities. Statistical analysis was conducted in Review Manager Version 5.3, and results were analysed and reported separately for breast and thoracic surgery subgroups. Results: Eighteen trials enroling 1141 patients were included. Overall, no significant difference was observed in time to rescue analgesia, with a mean difference of 0.69 h (95% confidence interval −1.83, 0.45; P = 0.24, I2 = 98%) between the SAP and TPV block groups. However, the TPV block demonstrated superior results for secondary outcomes in thoracic surgery patients. Complications related to the TPV block included pleural puncture and haematoma at the injection site. Conclusions: The evidence suggests that both blocks generally offer comparable analgesic efficacy for chest wall surgery patients, with the TPV block providing a slight advantage for those undergoing thoracic surgery.